MANAJEMEN DAN STRATEGI DAKWAH MUHAMMADIYAH KOTA SEMARANG - Arsam, Arsam (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2010)
Muhammadiyah is a missionary organization that invites people to do good and prevent the unjust act (amarma'ruf nahi munkar) to survive in the world and the hereafter. For propaganda purposes is working well, then theMuhammadiyah apply some strategy and good management and integrated mission. Among these strategies are: truststrategy, the administration strategy, economic strategy, a strategy of education, social welfare strategy, and a strategy fordistributing and broadcasting of Islam. The strategy developed by Muhammadiyah in order to attract people and also to befree from negative impacts caused by globalization